1999
DOI: 10.1093/treephys/19.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Freezing cycles enhance winter injury in Picea rubens

Abstract: We examined changes in chlorophyll absorbency in red spruce (Picea rubens Sarg.) foliage in response to simulated freezing cycles. Current-year branch tips were collected from 16 trees on January 8, January 20, February 8 and February 26, 1996. Tissue was subjected to freezing cycle treatments with a minimum of -35 degrees C and a maximum of 3 degrees C for a one-cycle treatment, and -9, -6, -3, 0 or 3 degrees C for four-cycle treatments. Samples were frozen at a rate of 5 degrees C h(-1), and warmed at 12 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Faxon fir trees are notably shallow rooting, with a large percentage of fine roots in the upper 30 cm (Schenk and Jackson 2002), and low winter-season temperatures may cause freezing injury to roots, promoted by frost penetration in the absence of adequate snow cover (Auclair et al 2010). Sakai and Larcher (1987) found that tree roots in northern hardwoods are by far the least affected by frost hardening of any tree tissue and can freeze at as little as -1°C, and the importance of soil frost as the foremost mechanism of dieback in northern hardwoods remains the most compelling explanation to date (Kullman 1991;Boyce 1995;Lund and Livingston 1999;Auclair et al 2010). Root kill exacerbates the effects of drought in the following growing season, and Faxon fir winter injury is caused by cold stress and (or) winter desiccation, which may result in the abscission of the most recent needles (Friedland et al 1984;Jalkanen et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Faxon fir trees are notably shallow rooting, with a large percentage of fine roots in the upper 30 cm (Schenk and Jackson 2002), and low winter-season temperatures may cause freezing injury to roots, promoted by frost penetration in the absence of adequate snow cover (Auclair et al 2010). Sakai and Larcher (1987) found that tree roots in northern hardwoods are by far the least affected by frost hardening of any tree tissue and can freeze at as little as -1°C, and the importance of soil frost as the foremost mechanism of dieback in northern hardwoods remains the most compelling explanation to date (Kullman 1991;Boyce 1995;Lund and Livingston 1999;Auclair et al 2010). Root kill exacerbates the effects of drought in the following growing season, and Faxon fir winter injury is caused by cold stress and (or) winter desiccation, which may result in the abscission of the most recent needles (Friedland et al 1984;Jalkanen et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Similar reductions in frost tolerance were observed by Strimbeck et al (1995) in mature trees. This rapid dehardening, unique to red spruce, is less pronounced if the period of thawing is brief (DeHayes et al 1990a, Perkins et al 1993 and if night-time temperature remains below 0°C (Hadley and Amundson 1992, Schaberg et al 1996, Lund andLivingston 1998). Therefore, periods of abnormally warm temperatures during the winter (DeHayes et al 1990a, DeHayes 1992, Hadley et al 1993b, followed by subfreezing temperatures (Strimbeck and DeHayes 2000), repeated freeze-thaw cycles (Lund and Livingston 1998) and direct sun exposure (Lazarus et al 2006) are frequent causes of frost damage.…”
Section: Frost Susceptibilitymentioning
confidence: 99%
“…Because red spruce grows in regions where air temperatures usually remain below O°C throughout the winter, extended thaws that allow melting and mobilization of water in the plant may stimulate precocious dehardening. Freezing injury would be expected if a prolonged thaw is followed by extreme cold or another form of cold stress resulting from temperature fluctuations, such as rapid freezing or repeated freeze-thaw cycles (Perkins and Adams, 1995;Lund and Livingston, 1998). Such environmental changes could conceivably lead to physiological impairment that may alter the phenological development and/or the full extent of cold tolerance achieved by northern montane red spruce trees, thereby increasing susceptibility to freezing injury.…”
Section: Physiological and Environmental Causes Of Freezing Injury Inmentioning
confidence: 99%
“…That is, laboratory estimates more likely overestimate cold tolerance because the systematic and controlled nature of laboratory freezing conditions (e.g., slow and consistent rate of freezing and thawing) potentially represents a less stressful set of conditions than the natural environment, which includes a diverse and interacting set of environmental conditions and inconsistent fluctuations in ambient temperatures. Data from Lund and Livingston (1998), for instance, suggest that multiple freeze-thaw events, which are common under ambient conditions, may enhance the freezing injury susceptibility of red spruce. Thus, T, would be expected to be higher under ambient conditions in which temperatures fluctuated above and below freezing.…”
Section: Relevance Of Cold Tolerance Estimates To Actual Injury Tempementioning
confidence: 99%